INNOVATIVE METHODOLOGICAL APPROACHES IN TEACHING CHEMISTRY IN HIGHER - Botirova Sabogul Rahmatullayenna (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
This article discusses innovative and effective methodological approaches used in teaching chemistry in higher education institutions. The study is based on the professional pedagogical experience of the author at the Department of Chemistry of Navoi State University. Particular attention is paid to student-centered learning, interactive methods, problem-based learning, digital technologies, and experimental-practical integration. The effectiveness of these methods in improving students’ analytical thinking and subject competence is analyzed. The results of the study show that the integration of modern pedagogical technologies into the chemistry curriculum significantly increases students’ motivation and academic performance.